W oczekiwaniu na niepodległość. Stanowisko lubelskiej „Szkoły Polskiej” (1916-1918) wobec edukacji narodowej - Michalska , Iwonna (Studia Edukacyjne, 2019)
This work reconstructs opinions concerning national education in independent Poland presented in 1916-1918 in the magazine titled Szkoła Polska (Polish School) – a body of a local division of Stowarzyszenie Nauczycielstwa Polskiego (Polish Teachers’ Association) in Lublin. The main goal of education was understood as instilling patriotism in the young generation of Poles based on their own most valuable achievements rather than on remembrance of injuries and persecution suffered at the hands of the enemy. It was believed that the memory of the past should be cherished, yet it could not dominate the present and the future. It was demanded that 7-year obligatory elementary schools should be established as well as 4-year secondary schools and 3-4-year occupational schools. What was deemed important was the need to involve illiterate adults in mandatory schooling and to provide additional education to graduates. It was maintained that the reborn Polish education system should be open to the latest pedagogical trends and, most of all, it should replace verbalism and teaching from books with teaching through experience. It was the teachers that were supposed to guarantee good education of children and teenagers, as they were active, creative, independent, had requisite professional qualifications, and were willing to self-educate.